Feather mites of the subfamily Pterodectinae (Acariformes: Proctophyllodidae) from passerines and kingfishers in Canada - Mironov, Sergey V.; Galloway, Terry D. (Zootaxa, 2021)
Investigation of the diversity and taxonomy of feather mites of the subfamily Pterodectinae (Astigmata: Proctophyllodidae) on passerines (Passeriformes) and kingfishers (Coraciiformes: Alcedinidae) in Manitoba revealed 19 species in 5 genera. Of them, eight new species are described, seven of these from passerines and one from a kingfisher: Alaudicola eremophila sp. n. from Eremophila alpestris (Alaudidae), Amerodectes icteri sp. n. from Icterus galbula (Icteridae), A. pheucticus sp. n. from Pheucticus ludovicianus (Cardinalidae), A. tiffanyluiae sp. n. from Oporornis agilis (Parulidae), A. tretiakae sp. n. from Molothrus ater (Icteridae), Tyrannidectes sealyi sp. n. from Tyrannus tyrannus (Linnaeus, 1758) (type host) and Tyrannus verticalis Say, and T. empidonicus sp. n. from Empidonax minimus (Tyrannidae), and Proterothrix megaceryle sp. n. from Megaceryle alcyon (Alcedinidae). Additionally, nine pterodectine species are reported for the first time in the fauna of Canada. Based on re-evaluation of diagnostic charcters, new diagnoses are proposed for the genera Amerodectes, Tyrannidectes, and Metapterodectes, and species contents of these genera are revised. Four species are transferred from the genus Amerodectes to Tyrannidectes with the new combinations proposed: T. caribaeus (Mironov and González-Acuña, 2011) comb. n., T. charitomenos (Hernandes, 2018) comb. n., T. pitangi (Mironov, 2008) comb. n., T. vireonis (Hernandes and Pedroso, 2016) comb. n. Six species are transferred from the genus Tyrannidectes to Metapterodectes with the new combinations: M. amaurochalinus (Hernandes and Valim, 2006) comb. n., M. cinclodes (Mironov and González-Acuña, 2011) comb. n., M. crassus (Trouessart, 1885) comb. n., M. falcklandicus (Mironov and González-Acuña, 2011) comb. n., M. fissuratus (Hernandes and Valim, 2005) comb. n., and M. pteroptochi (Mironov and González-Acuña, 2015) comb. n.